Nucleosome organization of mouse embryos during pre-implantation development - Zeng, Jitao; Tu, Xiaojuan; Qu, Siming; Chen, Xichan; Wang, Ying; Liu, Xiaona; Kang, Enchuan; Tian, Yi; Xiang, Qianming; Lai, Binbin; Gao, Weiwu; Ni, Bing; et al. (Scientific reports, 2025)
Sexual reproduction begins with sperm–oocyte fusion to form a zygote, where chromatin undergoes dramatic reorganization to establish totipotency. Although nucleosomes- the basic units of eukaryotic chromatin and key epigenetic regulators- are extensively remodeled during early embryogenesis, their dynamic repositioning mechanisms and biological implications remain unclear. Here, we employed single-cell MNase sequencing (scMNase-seq) to map genome-wide nucleosome positioning and chromatin accessibility in individual mammalian embryos. We found that nucleosome positioning mirrored somatic cell patterns until the 4-cell stage, with nucleosome depletion and phasing at CTCF sites not fully established until morula formation. By integrating H3K4me3 localization and transcriptomic data, we revealed that nucleosome sparsity at transcription start sites (TSS) and flanking regions correlated with expression levels of genes critical for preimplantation development. Notably, these nucleosome-depleted regions likely serve as regulatory hubs influencing histone modification dynamics. Our study systematically delineates nucleosome reorganization principles during mammalian embryogenesis and provides a high-resolution resource for understanding chromatin remodeling in early development.